THE EFFECT OF LEARNING CELL TECHNIQUE ON STUDENT'S READING COMPREHENSION - Nurmahyuni Asrul; Dorlan Juliana Silitonga; Mutia Oktavia Tarigan; Aprida Barus (Jurnal Education and Development, 2021)
The research objective was to find the effect significantly of the use of the Learning Cell Technique towardsthe students’ reading comprehension. The research population was the tenth grade students of SMAS PUTERI SION. The researchersappliedthe experimental research. It was done by applying the experimental group and the controlled group with quantitative approach. The population of the research was 40 students. The students’ total scores in the post-test in the experimental was 1,610 and 80.50 was the mean score of the students. It was found out that the total score from the post-test in controlled group was 1,225 and the mean score of the students was 61.25. The data consisted of independent sample of the t-test and it was stated that the t-test was higher than the t-table (t-test = 7.931> t-table = 3.319). The significance (p) was 0.001. The significance confirmed that 0.001 is lower than 0.005 (p < 0,005). This research had conclusion that H1was accepted and H0was rejected. The research findings were significant because p<0.05. From the result as presented above, there is a conclusion that the Learning Cell Technique significantly affected the students’ reading comprehension.